A Tripartite Game-Theory-Based Cooperation Mechanism for the Electronic Warehouse Receipt Pledge Financing Mode - Junwei Jia; Haoyue Zhang; Qi Wang (Discrete Dynamics in Nature and Society)
To explore the electronic warehouse receipt pledge financing cooperation mechanism in the alliance formed between loan enterprises, commercial banks, e-commerce platforms, and logistics enterprises, by constructing a tripartite evolutionary game model, the game equilibrium strategy is then obtained, and the influencing factors of the cooperation mechanism are further simulated. It was found that in this tripartite evolutionary game, the stable strategy combination occurs when the loan enterprise chooses to repay on time, the platform alliance chooses to provide services, and the commercial bank chooses to continue to cooperate. However, heterogeneity exists in the influencing factors for the three-party selection strategy in the game, which is manifested in the fact that the higher the realization rate of the pledge, the more evolution is required in the selection strategy for loan enterprises to continue cooperating. The higher the information service fee, the higher the enthusiasm of the platform alliance in choosing to provide services. Credit levels, loan interest rates, and pledge realization rates are all important factors that affect the choice strategy of commercial banks.